THE USE OF TREE DIAGRAM TECHNIQUE TO IMPROVE STUDENTS' WRITING ABILITY - Tuti, Tuti (English Language Education Study Program, 2023)
The main problem of this research was the students participation and writing ability are still low. The objective of this research is to recognize the improvement in students participation and to describe the improvement of students writing ability in learning activities through the implementation of Tree Diagram techniques. The subject of this research is the students of the tenth grade consisting of 30 students, 15 males and 15 females. Data from both qualitative and quantitative sources were used in this Classroom Action Research (CAR) study. While the authors employed tests to gather student test scores for quantitative data, they obtained qualitative data through observation, interviews, field notes, and documentation. The results showed that there was a positive increase in both students participation in learning to write and students ability to write descriptive texts. This can be seen from the results of observation checklists, field notes, and interviews showing that tree diagrams can increase students participation in learning to write. In cycle II the checklist observation results were 89.5%. The students writing results were also good, with an average score of 81.51. The researcher concluded that the Tree Diagram Technique was successful in increasing students' participation and ability to write.